2010
DOI: 10.1111/j.1399-3038.2009.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of lower leg and height growth in children with asthma treated with inhaled budesonide from a new dry powder inhaler

Abstract: Short-term knemometry is a highly sensitive and accurate method for non-invasive assessment of systemic activity of inhaled corticosteroids in children with asthma. However, there are no randomized data available to elucidate the relation between inhaled corticosteroid suppressed short-term lower leg and height growth. The aim of the present study was to assess the relation between short-term lower leg and 1-yr height growth in children with asthma treated with inhaled budesonide from the new Pulairmax inhaler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…CFC+S, chlorofluorocarbon pressurized metered dose inhaler with a spacer; CFC, chlorofluorocarbon pressurized metered dose inhaler without a spacer; HFA+S, hydroflouroalkane-134a pressurized metered dose inhaler with a spacer; HFA, hydroflouroalkane-134a pressurized metered dose inhaler without a spacer; DP, dry powder inhaler. randomized, parallel group trial of inhaled budesonide 200 lg from the Pulaimax Ò dry powder inhaler reported in the present issue of the journal are very consistent with the analysis (43). The mean 2-wk lower leg growth rate was 0.17 mm/wk in the budesonide group compared with 0.39 mm/wk in the montelukast group, thus representing a 44% suppression.…”
Section: Short-term Knemometry Implications For Intermediateterm Heightsupporting
confidence: 83%
See 1 more Smart Citation
“…CFC+S, chlorofluorocarbon pressurized metered dose inhaler with a spacer; CFC, chlorofluorocarbon pressurized metered dose inhaler without a spacer; HFA+S, hydroflouroalkane-134a pressurized metered dose inhaler with a spacer; HFA, hydroflouroalkane-134a pressurized metered dose inhaler without a spacer; DP, dry powder inhaler. randomized, parallel group trial of inhaled budesonide 200 lg from the Pulaimax Ò dry powder inhaler reported in the present issue of the journal are very consistent with the analysis (43). The mean 2-wk lower leg growth rate was 0.17 mm/wk in the budesonide group compared with 0.39 mm/wk in the montelukast group, thus representing a 44% suppression.…”
Section: Short-term Knemometry Implications For Intermediateterm Heightsupporting
confidence: 83%
“…So, although no specific cut‐off level can be identified in individuals from the available randomized, double‐blind short‐term knemometry and intermediate‐term height growth rate studies, good evidence have been provided that if the short‐term lower leg growth suppression in populations of children is higher than approximately 25% the risk of intermediate‐term growth suppression becomes significant with a mean height growth rate retardation in the range of approximately 0.5–1.5 cm during the first year of treatment (35). The results of the 1‐yr randomized, parallel group trial of inhaled budesonide 200 μg from the Pulaimax ® dry powder inhaler reported in the present issue of the journal are very consistent with the analysis (43). The mean 2‐wk lower leg growth rate was 0.17 mm/wk in the budesonide group compared with 0.39 mm/wk in the montelukast group, thus representing a 44% suppression.…”
Section: Short‐term Knemometry Implications For Intermediate‐term Heightmentioning
confidence: 99%
“…However, once-daily morning budesonide dosing of 200 µg administered through a DPI slowed growth by 1 cm over 1 year compared with growth seen in prepubertal peers receiving montelukast, suggesting even once-daily morning dosing can impose growth suppression. E8 …”
Section: Reviewmentioning
confidence: 99%
“…Mean 2-weeks lower leg growth rate was 0.17 mm/week in the budesonide and 0.39 mm/week in the montelukast treated children (p = 0.02). Mean 1-year height growth rate was 5.51 cm/year in the budesonide and 6.51 cm/year in the montelukast group [ 54 ]. A recent study by Zeiger et al .…”
Section: Budesonide (Bud)mentioning
confidence: 99%